Development of the tourism mobile application in Malaysia / Syed Abdullah Syed Abdul Kadir - Syed Abdul Kadir, Syed Abdullah (2016)
Abstract - Malaysia is well known as the most diverse as its culture. Besides the religious events, multi languages from different ethnic and the building architecture, there is a need for mobile applications to help the tourist to discover about it. There is a lot of tourist information in this country and most of it is conservative printed information and maps. This none green environment issue can be obtain by having a travel mobile application that supports the tourism information and travel features to ease the user to be more convenient travel with technology. To address this issue, the project tends to identify the lack of travel mobile application in Malaysia and to discover the recommendation from the interview from the international tourist at the airport. The interview discover about the tourism in Malaysia, development of the mobile application and also the features in travel mobile application that are needed to be develop to help the high demand of travel mobile application in Malaysia. The results showed that there are major suggestion the travel mobile application are needed to ease the tourist to find the tourist hotspot, navigation to the places using maps in smartphone and it's time to move to paperless environment. To improve the updated information about the historical places, sightseeing and also the hospitality information thus can enhance the performance and stability of the travel mobile application. u